Direct delivery of antigens to dendritic cells via antibodies specific for endocytic receptors as a promising strategy for future therapies - Lehmann, Christian; Heger, Lukas; Heidkamp, Gordon Frederik; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Dudziak, Diana (Vaccines, 2016)
Dendritic cells (DCs) are the most potent professional antigen presenting cells and are therefore indispensable for the control of immunity. The technique of antibody mediated antigen targeting to DC subsets has been the basis of intense research for more than a decade. Many murine studies have utilized this approach of antigen delivery to various kinds of endocytic receptors of DCs both in vitro and in vivo. Today, it is widely accepted that different DC subsets are important for the induction of select immune responses. Nevertheless, many questions still remain to be answered, such as the actual influence of the targeted receptor on the initiation of the immune response to the delivered antigen. Further efforts to better understand the induction of antigen-specific immune responses will support the transfer of this knowledge into novel treatment strategies for human diseases. In this review, we will discuss the state-of-the-art aspects of the basic principles of antibody mediated antigen targeting approaches. A table will also provide a broad overview of the latest studies using antigen targeting including addressed DC subset, targeted receptors, outcome, and applied coupling techniques.
Created from Fastlane, Scopus look-up
Keywords: Antigen targeting; Antigen targeting antibodies; Cancer; CLR; DC; DCIR; DEC205; Dendritic cell subsets; moDC; Vaccine